Nerve biopsy: Current indications and decision tools. Issue 2 (25th February 2021) - Nathani, Dev; Spies, Judith; Barnett, Michael H.; Pollard, John; Wang, Min‐Xia; Sommer, Claudia; Kiernan, Matthew C.
Abstract: After initial investigation of patients presenting with symptoms suggestive of neuropathy, a clinical decision is made for a minority of patients to undergo further assessment with nerve biopsy. Many nerve biopsies do not demonstrate a definitive pathological diagnosis and there is considerable cost and morbidity associated with the procedure. This highlights the need for appropriate selection of patients, nerves and neuropathology techniques. Additionally, concomitant muscle and skin biopsies may improve the diagnostic yield in some cases. Several advances have been made in diagnostics in recent years, particularly in genomics. The indications for nerve biopsy have consequently changed over time. This review explores the current indications for nerve biopsies and some of the issues surrounding its use. Also included are comments on alternative diagnostic modalities that may help to supplant or reduce the use of nerve biopsy as a diagnostic test. These primarily include extraneural biopsy and neuroimaging techniques such as magnetic resonance neurography and nerve ultrasound. Finally, we propose an algorithm to assist in deciding when to perform nerve biopsies.